Community fish refuge (CFR) pond monitoring: surface and groundwater study at Sras Ang CFR, Prey Veng Province, Cambodia - Oeurng, C.; Sok, T.; Hout, M. H.; Ich, I. (International Water Management Institute, 2024)
This technical report delves into the essential task of gathering validation data, focusing on surface and groundwater related data monitoring through the deployment of field equipment. The primary objective is to comprehensively monitor surface water and groundwater levels, along with rainfall, on a regular basis. This hydrologic monitoring initiative is conducted within the context of a case study centered on rice-fish systems, specifically community fish refuges (CFRs) in Prey Veng Province, Cambodia.